2016
DOI: 10.1038/srep30029
|View full text |Cite
|
Sign up to set email alerts
|

ω-3 PUFAs ameliorate liver fibrosis and inhibit hepatic stellate cells proliferation and activation by promoting YAP/TAZ degradation

Abstract: Elevated levels of the transcriptional regulators Yes-associated protein (YAP) and transcriptional coactivators with PDZ-binding motif (TAZ), key effectors of the Hippo pathway, have been shown to play essential roles in controlling liver cell fate and the activation of hepatic stellate cells (HSCs). The dietary intake of omega-3 polyunsaturated fatty acids (ω-3 PUFAs) has been positively associated with a number of health benefits including prevention and reduction of cardiovascular diseases, inflammation and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 51 publications
3
55
0
Order By: Relevance
“…In the current study, combined with the significant decrease in collagen fibers demonstrated in Masson trichrome stain (F2), there was a significant reduction in α-SMA and TIMP-1 expression in group III as compared to that in group II. In line with our results, Zhang et al 2016 [36] reported that omega-3 fatty acids down-regulate the expression of profibrogenic genes in activated HSCs by inducing degradation of their transcriptional regulator; Yes-associated protein (YAP) in a proteasome dependent manner. In addition, omega-3 fatty acids exerted a potent anti-fibrotic effect in the models of cardiac and pulmonary fibrosis [37,38] .…”
Section: Discussionsupporting
confidence: 92%
“…In the current study, combined with the significant decrease in collagen fibers demonstrated in Masson trichrome stain (F2), there was a significant reduction in α-SMA and TIMP-1 expression in group III as compared to that in group II. In line with our results, Zhang et al 2016 [36] reported that omega-3 fatty acids down-regulate the expression of profibrogenic genes in activated HSCs by inducing degradation of their transcriptional regulator; Yes-associated protein (YAP) in a proteasome dependent manner. In addition, omega-3 fatty acids exerted a potent anti-fibrotic effect in the models of cardiac and pulmonary fibrosis [37,38] .…”
Section: Discussionsupporting
confidence: 92%
“…They showed that blocking Hh signaling in HSCs inhibited activation of YAP, and deletion of YAP in HSCs suppressed Hh signaling, suggesting that Hh and YAP interact to maintain the MF-phenotype in HSCs. In addition, both Hh and YAP signaling were shown to be associated with TGFb in HSC activation and liver carcinogenesis [16,[62][63][64]. Compared with the 10% infection groups, a greater increase of TGFβ and αSMA protein in the 30% infection groups appears to have been promoted by enhanced YAP activity, suggesting the possibility that YAP accelerates HSC activation.…”
Section: Discussionmentioning
confidence: 90%
“…So, our findings support the notion that TAZ localization could play a significant role in the causation of liver cirrhosis. Speculatively, an increase in the levels of TAZ may represent a posttranscriptional mechanism, because there was no significant difference in the expression of WWTR1 mRNA between cirrhotic and control I subjects . Also, other probable reasons for this observation might be the differences in the in vivo half‐lives of TAZ or a possible error in both protein and mRNA experiments .…”
Section: Discussionmentioning
confidence: 98%